A Study of Teacher Influence in the Classes of Primary School Teachers vis-a-vis Emotional Intelligence and Demographic Variables - Tiwari, Gaurang; Pandey, Asha (INDIAN EDUCATIONAL REVIEW, 2014)
Effects of Emotional Intelligence (EI) and demographic variables have been examined on teacher influence. I/D ratios of teachers as per Flanders (1970) were treated as indices of teacher influence in classroom. Study revealed that level of EI of teachers affects teacher influence (I/D ratio) significantly. Effects of demographic variables like: training, stream (art and science) and sex have been found to be insignificant. Type of school (government and private) is observed to affect teacher influence significantly and observed to moderate association between EI of teachers and teachers’ I/D ratios. Due to significant effect of EI on teacher influence (I/D ratio or Indirectness/Directness) of primary school teachers, it is likely to be concluded that teacher high on emotional intelligence will exert “Indirect Teacher Influence” while teaching.Introduction.